A 19-Year Experience With Clavicular Defects: An Algorithm for Flap Selection and Surgical Outcomes. Issue 5 (May 2021) - Lim, Kaitlin Ann; Lin, Cheng-Hung; Lin, Chih-Hung
Abstract : Background: The clavicle contributes to the stability and functional integrity of the shoulder. Clavicle bone defects are uncommon, and the strategy for their management is variable. Method: Six patients presented with clavicle bone defects. The causes were as follows: traumatic defects (2 patients), electric injury (1 patient), osteoradionecrosis (2 patients), and nonunion (1 patient). One patient had upper limb palsy for 40 years, and another had posttraumatic shoulder function impairment. A pedicled pectoralis major myocutaneous flap was used for the patient with a dysfunctional limb, and 5 bone flaps (3 free fibular flaps, 1 free iliac flap, and 1 pedicled rib flap) were used for reconstruction in the other patients. Result: All flaps (2 pedicled flaps and 4 free flaps) were successfully used for wound repair; the pedicled rib flap demonstrated partial marginal necrosis, and the free fibular flap required reexploration for venous kinking. Five functionally impaired upper limbs showed functional improvements postoperatively. Conclusion: For functionless composite clavicles and soft tissue defects, a soft tissue flap will be required for wound repair. A bone flap, especially a fibular flap, is required for the upper limb to show functional recovery. The variety of flaps will be planned according to the defect size comparison between the bone and soft tissue, and ipsilateral upper limb function, and a proposed algorithm will be discussed.